Importance of Knowing the Normality of the Data Used in Research Work by Thesis Students (Docentes 2.0 Journal, 2024)
Knowing the normality of data in research papers is essential in choosing the appropriate methods to analyze them and obtain valid and reliable conclusions. The research objective was to know the importance of the normality test in research papers as a previous protocol to choose the statistical test to contrast the hypothesis. The research was based on the hypothetical-deductive method, positivist paradigm, with a quantitative approach, non-experimental design, and descriptive type, with a population and sample of 10 recent investigations that address the statistical normality of the data as the main theme. The techniques and instruments used in this research include bibliographic review and content analysis. The results reveal that using numerical and graphic methods allows a more complete evaluation of the normality of the data. Both approaches are advisable to understand the data distribution better and make informed decisions. The main discussion is that sample sizes under 50 should use the Shapiro-Wilk test. In conclusion, the normality test is important in choosing the statistical procedure for testing hypotheses in a research paper, which influences the results' validity.
Keywords: Data normality; research papers; thesis; normality assumptions; normal distribution